Pengaruh Career Development dan Work-life Balance Terhadap Turnover Intention dengan Employee Engagement Sebagai Variabel Intervening Pada PT. Millennium Elektrik Indonesia - Rochmawati, Septiana; Utaminingsih, Adijati; Widhiastuti, Hardani (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The purpose of this study is to examine the effect of career development on employee engagement, the effect of work-life balance on employee engagement, the effect of career development on turnover intention, the effect of work-life balance on turnover intention, the effect of employee engagement on turnover intention, the effect of career development on turnover intention through employee engagement as an intervening variable, and the effect of work-life balance on turnover intention through employee engagement as an intervening variable. This study uses a quantitative method. The sample consists of 125 employees of PT. Millennium Elektrik Indonesia, using census sampling technique where the entire population is used as the sample. Data analysis in this study is conducted using the SmartPLS application with the Structural Equation Modeling (SEM) Partial Least Squares (PLS) method. The results of this study indicate that (1) career development has a positive and significant effect on employee engagement, (2) work-life balance has a positive and significant effect on employee engagement, (3) career development has a positive and significant effect on turnover intention, (4) work-life balance has a positive and significant effect on turnover intention, (5) employee engagement has a positive and significant effect on turnover intention, (6) career development has a positive and significant effect on turnover intention through employee engagement as an intervening variable, (7) work-life balance has no effect on turnover intention through employee engagement as an intervening variable.